Satiety, glycemic profiles, total antioxidant capacity, and postprandial glycemic responses to different sugars in healthy Malaysian adults - Azlan, Azrina; Ebadi, Samarghand; Mohd Yusof, Barakatun Nisak; Othman, Nur Maziah Hanum; Kannar, David; Sultana, Sharmin; Mahmood, Zhafarina (Elsevier, 2022)
Objectives: We investigated a low-glycemic index (GI), minimally refined brown sugar (MRBS) that retains a consistent amount of antioxidant polyphenols. This study aimed to determine whether MRBS has a lower postprandial glycemic response and GI value compared with other types of refined sugar (RS). Low glycemic response foods are also reported to increase satiety. Accordingly, we also evaluated satiety profiles, glycemic profiles (glucose, insulin, and glucagon), and total antioxidant capacity (TAC). Methods: This work shows the results of two single-blind, cross-over studies (studies 1 and 2). For each study 14 healthy Malay individuals with a normal body mass index were recruited. In study 1, capillary blood samples were used to determine the GI of the tested sugars. Venous blood samples were used in study 2 to measure the concentrations of satiety hormones (peptide tyrosine, C-peptide, glucagon-like peptide-1, and leptin), TAC, plasma glucose, insulin, and glucagon concentrations at baseline (0 min) and at 60 and 120 min after consumption of the MRBS and RS formulated jellies. Results: The incremental area under the curve of glucose positive control (312 ± 62.54 mmol.min/L) was significantly higher than that of other types of sucrose (P < 0.05). MRBS (GI: 54 ± 4.5 mmol.min/L) and brown sugar (GI: 50 ± 5.0 mmol.min/L) were categorized as low GI, and RS (GI: 64 ± 5.73 mmol.min/L) was in the medium category, which was significantly lower than the GI of glucose (GI: 100 mmol.min/L; P < 0.05). Likewise, there was a significant difference in satiety profiles (peptide tyrosine and C-peptide), glycemic profile (glucagon), and TAC (P < 0.05) between RS and MRBS jellies. Conclusions: The results of our work show that MRBS had a lower GI (study 1), and better satiety, glycemic profiles, and TAC (study 2) compared with RS.